Comparison Of Critical Thinking Among Librarians Of Shiraz Universities - Fatemeh Motamedi; Parvin Bagheri; Ebrahim Emami (پیاورد سلامت, 2015)
Background and Aim: Critical thinking helps to raise awareness and knowledg e growth by applying the mental processes such as analysis , inference and reasoning. So, it provides an appropriate context for problem solving as well as clear and accurate information-based decision making in different managerial and political areas. The aim of this study was to assess and compare academic librarians in terms of having critical thinking skills. Materials and Methods: This is a descriptive- analytical survey that was conducted cross- sectionally on 95 librarians working in Shiraz University and Shiraz University of Medical Sciences by Census method. Data collect ion was conducted through the translated version of t he standard questionnaire of California critical thinking skills test: form B., that its validity and reliability have also been proved (validity according to subject specialists: 80-84% and Cronbach's reliability test : 74%). For descriptive analysis of data obtained from 68 completed questionnaires, the descriptive statistics using frequency distribution tables , mean and standard deviation and for inferential analysis SPSS software , t- test , ANOVA, Pearson correlation coefficient and spearman were used . Results: There was no significant difference between the two groups of librarians , in terms of different sections of critical thinking . There was no relationship between age and job tenure and critical thinking, While there was a significant difference between sex and degree with critical thinking. Conclusion: The results of this study and other similar studies can provide useful information to develop the critical thinking skills in academic librarians and help the academic excellence in our country .